Kant and the Transformation of Natural History - Cooper, Andrew 1986- (Oxford University Press, Incorporated, 2023)
Andrew Cooper presents the first systematic study of Kant's account of natural history. Cooper contends that Kant made a decisive contribution to one of the most explosive and understudied revolutions in the history of science: the addition of time to the frame in which explanations are required, sought, and justified in natural science